Pendidikan Islam dalam Mengatasi Degradasi Moral Remaja di Era Digital - Putri Durrotul Fadhila (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2024)
Moral degradation among adolescents in the digital era is becoming an increasingly serious problem. This is in line with the rapid development of technology that makes teenagers easily exposed to various content that can affect their values and behavior. The purpose of this study is to find out how Islamic education can help overcome the moral decline of adolescents in the digital era. By looking at various relevant materials, such as books, papers, and scientific journals that discuss Islamic education and the influence of social media on adolescent morals, the research methodology used is library research. The results show that Islamic education has great potential in shaping the character and morals of adolescents, especially through teaching religious values that can lead them to a better understanding of ethics and morals so that they do not fall into the negative influence of the digital world. The implication of this research is the need for a more adaptive Islamic education strategy to effectively guide adolescents in facing moral challenges in the digital era. An approach that involves family, school, community and digital media will help instill strong moral values in adolescents.